Reconciliation of Ulama and Umara in Socio-Political Conflict through Sufistic Approach - Hilmi Ridho; Mirwan Mirwan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
Ulama have a role as cultural and moral figures to protect and foster people in social life. Umara is a political elite tasked with carrying out state political policies and maintaining state ideology. In the socio-political context, the ulama and umara synergize with each other to realize the unity and harmony of the people in religion and the state. In reality, some Islamic organizations led by ulamas create a commotion in the country and are very opposed to the umara policy, causing divisions among community groups. Based on the problems above, the study's results show that (1) the involvement of ulama and umara in the political stage is not new. That strong support from the Shari'a is exemplified by the Prophet Muhammad and Khulafa Ar-Rashidin. (2) Ulama and umara should create an ideal society, namely a society that is independent and runs on the correct principles. (3) Social Sufism offers a solution to overcome conflicts between ulama and umara amid society.